Infant/child rapid serology tests fail to reliably assess HIV exposure among sick hospitalized infants. (17th July 2017) - Wagner, Anjuli D.; Njuguna, Irene N.; Andere, Ruth A.; Cranmer, Lisa M.; Okinyi, Helen M.; Benki-Nugent, Sarah; Chohan, Bhavna H.; Maleche-Obimbo, Elizabeth; Wamalwa, Dalton C.; John-Stewart, Grace C.
Abstract : Background: The WHO guidelines for infant and child HIV diagnosis recommend the use of maternal serology to determine child exposure status in ages 0–18 months, but suggest that infant serology can reliably be used to determine exposure for those less than 4 months. There is little evidence about the performance of these recommendations among hospitalized sick infants and children. Methods: Within a clinical trial (NCT02063880) in Kenya, among children 18 months or younger, maternal and child rapid serologic HIV tests were performed in tandem. Dried blood spots were tested using HIV DNA PCR for all children whose mothers were seropositive, irrespective of child serostatus. We characterized the performance of infant/child serology results to detect HIV exposure in three age groups: 0–3, 4–8, and 9–18 months. Results: Among 65 maternal serology positive infants age 0–3 months, 48 (74%), 1 (2%) and 16 (25%) had positive, indeterminate and negative infant serology results, respectively. Twelve (25%), 0 and 4 (25%) of those with positive, indeterminate and negative infant serology results, respectively, were HIV-infected by DNA PCR. Among 71 maternal serology positive infants age 4–8 months, 31 (44%), 8 (11%) and 32 (45%) had positive, indeterminate and negative infant serology results, respectively. Fourteen (45%), 2 (25%) and 7 (22%) infants with positive, indeterminate and negative infant serology results, respectively, were HIV-infected. Among 67 maternal serology positive infants/children age 9–18 months, 40 (60%), 2 (3%) and 25 (37%) had positive, indeterminate and negative infant serology results, respectively. Thirty-six (90%), 2 (100%) and 2 (8%) infants with positive, indeterminate and negative infant serology results, respectively, were HIV-infected. In the 0–3, 4–8 and 9–18 month age groups, use of maternal serology to define HIV exposure identified 33% [95% confidence interval (CI) 10–65%], 44% (95% CI 20–70%) and 5% (95% CI 0.1–18%) more HIV infections, respectively. Conclusion: Maternal serology should preferentially be used for screening among hospitalized infants of all ages to improve early diagnosis of children with HIV.